Climate Change and Regional/Local Responses - Zhang, Yuanzhi; Ray, Pallav (IntechOpen, 2013)
Understanding climate change requires analysis of its effects in specific contexts, and the case studies in this volume offer examples of such issues. Its chapters cover tropical cyclones in East Asia, study of a fossil in Brazil's Araripe Basin and the fractal nature of band-thickness in an iron formation of Canada's Northwest Territories. One chapter examines the presence of trace elements and palynomorphs in the sediments of a tropical urban pond. Examples of technologies used include RS- GIS to map lineaments for groundwater targeting and sustainable water-resource management, the ALADIN numerical weather-prediction model used to forecast weather and use of grids in numerical weather and climate models. Finally, one chapter models sea level rises resulting from ice sheets melting.